Exploring Mental Wellbeing, Distress and Adjustment in a Blended Learning Environment - Conwi, Lord Joseas; Pinar, Fredyrose Ivan; Destura, Jose Jr. (Journal of Interdisciplinary Perspectives, 2024)
In the wake of the COVID-19 pandemic, the education landscape underwent a rapid transformation, with blended learning emerging as a predominant approach. This study employed explanatory sequential analysis to examine the impact of academic and familial distress, as well as adjustment, on students' mental health within the dual continua model. Quantitative results identified three mental health groups: flourishing (21.14%), languishing (39.72%), and moderately mentally healthy (39.14%). Students generally displayed moderate mental well-being, high academic distress, moderate familial distress, and strong adjustment to blended learning. Notably, the relationship between adjustment and academic stress, suggesting the effective adaptation to the demands of blended learning can mitigate academic related stressors. Explaining the quantitative area, qualitative exploration uncovers a deeper understanding of student’s lived experiences, emotional states, ranging from resilience and adaptability to anxiety and frustrations. Moreover, it tackles the challenges faced by the students including technological barriers, time management dilemmas and exacerbation of isolation as the effects of pandemic. These revelations underscore the imperative need for educational interventions that seamlessly integrate mental health education into curricula, fostering a healthier and more inclusive blended learning environment. Prioritizing mental health education in the curriculum can enhance students' academic, emotional, and social success in the evolving educational environment.